2007
DOI: 10.1007/s10439-007-9370-2
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity

Abstract: The aim of this study was to test the differentiative effects of osteoblasts after treatment with a static magnetic field (SMF). MG63 osteoblast-like cells were exposed to a 0.4-T SMF. The differentiation markers were assessed by observing the changes in alkaline phosphatase activity and electron microscopy images. Membrane fluidity was used to evaluate alterations in the biophysical properties of the cellular membranes after the SMF simulation. Our results show that SMF exposure increases alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 35 publications
6
58
0
Order By: Relevance
“…3, we also found that the proliferation rate of MG63 cells was inhibited by SMF exposure. These results confirmed previous findings that both the continuous SMF-and PEMF-stimulated osteoblasts expressed more ALP activity than control cultures [5,11,17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3, we also found that the proliferation rate of MG63 cells was inhibited by SMF exposure. These results confirmed previous findings that both the continuous SMF-and PEMF-stimulated osteoblasts expressed more ALP activity than control cultures [5,11,17].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, measurement of the contact angle of the injection-molded PLLA revealed no differences between the SMF-exposed and sham-exposed cell-free PLLA samples, suggesting the changes in cell behavior of MG63 cells on the PLLA substrates in this study (Figs. 3,4,5) were decoupled from the surface characteristics of the PLLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that cell adhesion onto scaffolds is an important step in tissue engineering [8,25]. Since previous studies have found that SMF have a positive effect on cellular proliferation and differentiation [9][10][11][12], it is not surprising that cells cultured on magnetized membranes demonstrate a more spreading morphology. Similar results can be found in several previous studies, which reported that magnetic nanoparticles exhibited a strongly osteoinductive effect [2,8,20].…”
Section: Resultsmentioning
confidence: 99%
“…For physical factors, static magnetic fields (SMF) have been reported as an inducer of osteoblastic differentiation [9][10][11][12]. It has also been reported that SMF had a significant effect on cell attachment and proliferation on to the surface of scaffold [10].…”
Section: Introductionmentioning
confidence: 99%